Educational Marketing Strategies Through Facebook and WhatsApp in Increasing Sales and Business Literacy in Home-Based Convection Businesses (Case Study: Ais Collection) - Saida Aprilia; Manah Tarman (Global Action and Education for Society, 2025)
This study aims to determine the marketing strategy of Konveksi Ais Collection via Facebook and WhatsApp and its impact on increasing sales. Using a descriptive qualitative approach, data obtained through interviews, observation, and documentation. The results of the study show that marketing through social media is effective in increasing sales. Before using this strategy, sales reach 150–160 products per month, and increased to 200–270 products after digital marketing was implemented. This strategy also has a positive impact on operations and employees.